Mapping of mobilizations of Bibliometrics and Scientometrics in Science Education research: a look at national journals (Research, Society and Development, 2020)
Bibliometrics approaches have been evolving in the last decades and providing theoretical and methodological tools of extreme relevance to the most diverse areas of knowledge. However, the area of Science Education Research apparently has not been broadly mobilizing such perspectives in their productions. In order to contribute to the advance of our understanding of these mobilizations, we seek to build a look at what has been produced in national journals present in the Qualis strata A1, A2 and B1, in the Teaching area of CAPES, seeking to answer the following questions: How have bibliometric/scientometric analyzes been used in articles from national journals linked to PEC in Brazil? Which agents have contributed to these productions? Thus, from a qualitative and quantitative approach, we organized the analyzes in two methodological moments: (i) analysis of bibliographic data (most recurrent journals, temporal distribution, most recurrent authors, areas of initial formation, institutions of initial formation, linking professional, postgraduate and advisor); and (ii) analysis of bibliographic references (reference format, most present journals, temporal distribution, languages, most cited references and citation networks). It was possible to find only 7 articles in 5 journals, reinforcing the incipience of bibliometric approaches in the context of the PEC, despite an apparent increase in recent years. It is evident the presence of two central cores that have been concentrating the efforts in the consolidation of these forms of approaches and points to the several possibilities still open, that can be explored for better knowledge of the authors of the PEC about the own constitution of the area.